Optimizing Growth and Yield of Napa Cabbage (Brassica rapa L.) Using Lamtoro Liquid Organic Fertilizer: Optimisasi Pertumbuhan dan Hasil Sawi Putih (Brassica rapa L.) dengan Menggunakan Pupuk Organik Cair Lamtoro - Masruroh, Chairil Isna; Abror, M; Nurmalasari, Intan Rohma (Indonesian Journal of Innovation Studies, 2023)
Napa cabbage, a leafy vegetable highly sought after by Indonesian consumers due to its rich content of pro-vitamin A, ascorbic acid, and fiber, was the subject of this study. The aim was to determine the most effective concentration of lamtoro liquid organic fertilizer on the growth and yield of napa cabbage plants. The research took place in Modong Village, Tulangan District, Sidoarjo Regency, with follow-up observations conducted at the Agrotechnology Study Program Laboratory during October-December 2022. A non-factorial Randomized Group Design (RBD) was employed, consisting of 7 treatments: P0 (control), P1 (5 ml/L), P2 (10 ml/L), P3 (15 ml/L), P4 (20 ml/L), P5 (25 ml/L), and P6 (30 ml/L). The experiment was repeated 3 times, resulting in 21 experimental units, and data analysis included the 5% BNJ test. Variables observed encompassed plant height, number of leaves, root length, wet weight, dry weight, and harvest index. The findings indicated that administering lamtoro liquid organic fertilizer at the highest dose of 30 ml/L had the most significant impact on plant height and leaf number in napa cabbage plants, while other parameters such as root length, fresh weight, dry weight, and harvest index were not significantly affected.  Highlights: Importance of Napa Cabbage: The abstract highlights the importance of Napa cabbage in Indonesia due to its high nutritional content, which includes pro-vitamin A, ascorbic acid, and high fiber. Effectiveness of Lamtoro Liquid Organic Fertilizer: The study aims to determine the best concentration of lamtoro liquid organic fertilizer on the growth and yield of napa cabbage plants. The study shows that the highest dose of 30 ml/L of lamtoro liquid organic fertilizer had the best effect on the growth of plant height and number of leaves. Experimental Design: The study used a non-factorial Randomized Group Design (RBD) with 7 treatments and was repeated 3 times to obtain 21 experimental units. The variables observed included plant height, number of leaves, root length, wet weight, dry weight, and harvest index. Keywords : Cabbage, Growth, Lamtoro Liquid Organic Fertilizer, Napa, Yield